2002
DOI: 10.1046/j.1365-313x.2002.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

An engineered phosphoenolpyruvate carboxylase redirects carbon and nitrogen flow in transgenic potato plants

Abstract: Phosphoenolpyruvate carboxylase (PEPC) plays a central role in the anaplerotic provision of carbon skeletons for amino acid biosynthesis in leaves of C3 plants. Furthermore, in both C4 and CAM plants photosynthetic isoforms are pivotal for the fixation of atmospheric CO2. Potato PEPC was mutated either by modifications of the N-terminal phosphorylation site or by an exchange of an internal cDNA segment for the homologous sequence of PEPC from the C4 plant Flaveria trinervia. Both modifications resulted in enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 47 publications
7
71
1
1
Order By: Relevance
“…It has been reported that expression of maize PEPC causes a slight reduction in net assimilation and stunting in transgenic rice plants (Taniguchi et al, 2008). Retarded growth that correlated with PEPC activity was also reported for potato (Solanum tuberosum; C 3 ) plants overexpressing a modified C 4 PEPC from Flaveria trinervia, and metabolite analysis of these plants revealed elevated levels of malate and total amino acids (Rademacher et al, 2002). Increases in malate and nitrogen content were also observed in maize PEPC-overexpressing rice plants (Agarie et al, 2002).…”
Section: Several Maize Transcripts Associated With C 4 Photosynthesismentioning
confidence: 66%
“…It has been reported that expression of maize PEPC causes a slight reduction in net assimilation and stunting in transgenic rice plants (Taniguchi et al, 2008). Retarded growth that correlated with PEPC activity was also reported for potato (Solanum tuberosum; C 3 ) plants overexpressing a modified C 4 PEPC from Flaveria trinervia, and metabolite analysis of these plants revealed elevated levels of malate and total amino acids (Rademacher et al, 2002). Increases in malate and nitrogen content were also observed in maize PEPC-overexpressing rice plants (Agarie et al, 2002).…”
Section: Several Maize Transcripts Associated With C 4 Photosynthesismentioning
confidence: 66%
“…of PEPC in transgenic potato (Solanum tuberosum) plants showed that the flux of soluble sugars and starch is directed to organic acids such as malate and the amino acids Glu and Gln (Rademacher et al, 2002). We surmised that a fruit such as tomato may also use a similar mechanism, i.e.…”
Section: Discussion Higher Polyamines May Control Multiple Sites In Cmentioning
confidence: 99%
“…Integration of glycolysis with N assimilation is likely linked with phosphoenolpyruvate carboxylase (PEPC), which provides C skeletons (Huppe and Turpin, 1994;Foyer and Noctor, 2002;Rademacher et al, 2002), and cytosolic isocitrate dehydrogenase is given as the sum of citrate (citr) and malate to that of Glc plus Fru plus Suc. These results were generated from the data given in Figure 2.…”
Section: Sustained Higher Respiration Rate In Transgenic Fruit Durinmentioning
confidence: 99%
“…Since pyruvate and PEP metabolites are transformed via the gluconeogenic pathway to sugar phosphates, which can subsequently be converted to starch (Lara et al, 2004), and the fact that previous studies demonstrated that phosphoenolpyruvate carboxylase (PEPC) activity plays an important role within potato (Solanum tuberosum) starch metabolism (Rademacher et al, 2002), we next evaluated the starch content of both the wild type and transformants at breaker stage (Fig. 5).…”
Section: Deficiency In Pepck and Nadp-me Leads To Alteration In Nuclementioning
confidence: 99%